DIGITAL ELEVATION MODEL FROM PRISM-ALOS AND ASTER STEREOSCOPIC DATA - Bambang Trisakti; Ita Carolita; Firsan Ardi Pradana (International Journal of Remote Sensing and Earth Sciences, 2009)
Digital Elevation Model (DEM) is a source to produce contour map, slope, and aspect information, which is needed for other information such as disaster and water resources management. DEM can be generated by several methods. One of them is parallax calculations from stereoscopic data of optical sensor. Panchromatic Remote-Sensing Instrument for Stereo Mapping (PRISM) sensor from Advanced LAnd Observation Satellite (ALOS) satellite and advance space borne Thermal Emission and Reflection Radiometer (ASTER) sensor from Terra Satellite is Japanese optical satellite sensor which have abilityto produce stereoscopic data. This study showed DEM generations from PRISM (2.5 m spatial resolution) and ASTER (15m spatial resolution) stereoscopic data using image matching and collinear model based on Orthobase-pro software. The Generated DEM from each sensor was compared to the DEM from Shuttle Radar Topography Mission (SRTM) X-C band with 30 m spatial resolution. The dependent on the pixel size from the DEM produced were also discussed. The result showed that both DEMs have similiar elevation and distribution pattern to the referenced DEM, but DEM for PRISM had higher relative accuracy (RMSE is 6.5 m) and Smoother pattern comparing to DEM from ASTER (RMSE is 10.2 m) Keyword : ASTER, DEM, PRISM, SRTM, Stereoscopic satellite data